2008
DOI: 10.1073/pnas.0709194105
|View full text |Cite
|
Sign up to set email alerts
|

Optimal vein density in artificial and real leaves

Abstract: The long evolution of vascular plants has resulted in a tremendous variety of natural networks responsible for the evaporatively driven transport of water. Nevertheless, little is known about the physical principles that constrain vascular architecture. Inspired by plant leaves, we used microfluidic devices consisting of simple parallel channel networks in a polymeric material layer, permeable to water, to study the mechanisms of and the limits to evaporationdriven flow. We show that the flow rate through our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
210
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(224 citation statements)
references
References 17 publications
8
210
2
Order By: Relevance
“…Understanding this coordination has undoubtedly improved our understanding of water use and photosynthesis, and has provided an impetus for new theoretical work (Noblin et al. 2008; Boyce et al. 2009; Boyce and Zwieniecki 2012; Brodribb et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding this coordination has undoubtedly improved our understanding of water use and photosynthesis, and has provided an impetus for new theoretical work (Noblin et al. 2008; Boyce et al. 2009; Boyce and Zwieniecki 2012; Brodribb et al.…”
Section: Resultsmentioning
confidence: 99%
“…2007; Noblin et al. 2008; Zwieniecki and Boyce 2014), although this relationship is likely shifted by leaf thickness (Noblin et al. 2008; Sack et al.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Price et al 14 proposed that vein density should be independent from leaf size, because a constrained distance between the minor veins and thus a high vein density is needed for water and sugar transport. This idea comes from physiological studies that showed such an importance of high vein density but also adaptive variation across species 4,43,[51][52][53] . Indeed, we found here a considerably higher and more variable range of values for total vein density (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…High VLA may also be associated with shorter vertical path length if VLA is negatively correlated with leaf thickness, as is observed within certain species sets and lineages but not others (Noblin et al, 2008;Sack et al, , 2014Zwieniecki and Boyce, 2014). However, K ox might be correlated with VLA due to the influence of other traits that are structurally associated with veins and are positively correlated with K leaf , such as the size and hydraulic permeability of BS cells and the presence and size of bundle sheath extensions (BSEs).…”
mentioning
confidence: 99%